(untitled) - Horvát, Jozef (Aura musica, 2021)
The paper contains a formal analysis of the vocal-instrumental composition Trinity Te Deum by the contemporary composer Ēriks Ešenvalds. The author focuses mainly on the characteristics of the choir part, specifying an analysis of the musical structure with accents on the disposition of the sung text, while also pointing out the musical symbolic interpretation of the work and its spiritual message.
Keywords: Ešenvalds; Te Deum; Trinity; sacred works; composer